2013
DOI: 10.1002/ccd.24725
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of type B dissection in patients with marfan syndrome: Mid‐term outcomes and aortic remodeling

Abstract: Our results suggest that TEVAR is feasible, safe, and associated with a high reintervention rate and reduced rate of positive aortic remodeling in patients with Marfan syndrome. Survival at 8 years was comparable to contemporary series of open repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 30 publications
4
27
0
2
Order By: Relevance
“…6 In contrast, Eid-Lidt et al achieved 100% primary technical success in a study on 89 patients with MFS with type B dissection who received TEVAR. 15 However, they reported not only a decreased rate of positive aortic remodelling, but also a high rate of secondary endoleaks (44%) and a re-intervention rate of 33%, which is comparable to the results of others. 3,5 Regarding open aortic repair, Ghanta et al reported data from 49 open type II TAAA repairs in patients with MFS with no deaths within 30 days of operation.…”
Section: Discussionsupporting
confidence: 81%
“…6 In contrast, Eid-Lidt et al achieved 100% primary technical success in a study on 89 patients with MFS with type B dissection who received TEVAR. 15 However, they reported not only a decreased rate of positive aortic remodelling, but also a high rate of secondary endoleaks (44%) and a re-intervention rate of 33%, which is comparable to the results of others. 3,5 Regarding open aortic repair, Ghanta et al reported data from 49 open type II TAAA repairs in patients with MFS with no deaths within 30 days of operation.…”
Section: Discussionsupporting
confidence: 81%
“…The available literature suggests that TEVAR can be unpredictable in patients with a connective tissue disorder and can result in poor outcomes [36][37][38][39]. In a previous study, we noted that in one young patient with a connective tissue disorder and chronic aortic dissection, the patient's aorta expanded extremely rapidly (nearly 4 cm in 3 weeks) after TEVAR [13].…”
Section: Patients With Connective Tissue Disordersmentioning
confidence: 94%
“…Waterman and colleagues reported their experience with 16 patients (5). The pertinent clinical data are summarized in Eid-Lidt and colleagues reported an experience with ten patients, all of whom presented with acute type B dissection with extension into the abdomen (DeBakey type IIIB) (6). Nine of the patients met "high risk" criteria for open repair, however, the criteria were not defined.…”
Section: Perspectivementioning
confidence: 99%